Game Modification Trial in the Learning Approach of Physical Education Material Passing Over Volleyball - Terik, Ajen Alpa; Kristina, Putri Cicilia; Kumbara, Hengki (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
Some of the modified games, then used as a physical education learning approach, are expected to affect the learning outcomes of the passing material over the student's volleyball game. The purpose of this study is to find out the effect of a modified playing approach on the learning outcomes of passing on volleyball games in grade VII students of SMP Padmajaya Palembang. This study uses an experimental method with a one group pretest-postest design research. The treatment was carried out on a group of 21 students who were taken through cluster random sampling techniques. The treatment is carried out in a time allocation of 3x3 lesson hours with three learning stages, namely introduction, core and conclusion. The data collection instrument uses affective, cognitive and psychomotor results of students in learning. Data analysis was carried out parametrically through paired sample t test analysis. The results showed that there was a change in the pretest value before treatment was 69.37, increasing after treatment to 73.97. Meanwhile, the results of the tcal hypothesis test were > ttable (3,136 > 1,724), thus the researcher concluded that there was a significant influence of the modified play approach on the learning outcomes of passing on the game of volleyball in grade VII students of Padmajaya Junior High School Palembang.